The Laplace operator on the Sierpinski gasket with Robin boundary conditions. (December 2017) - Breckner, Brigitte E.; Chill, Ralph
Abstract: We study the Laplace operator on the Sierpinski gasket with nonlinear Robin boundary conditions. We show that for certain Robin boundary conditions the Laplace operator generates a positive, order preserving, L ∞ -contractive semigroup which is sandwiched (in the sense of domination) between the semigroups generated by the Dirichlet–Laplace operator and the Neumann–Laplace operator. We also characterise all local semigroups which are sandwiched between these two extremal semigroups by showing that their generators are Robin–Laplace operators.